Physical Education, Sports And Health In Forming Tolerance Attitudes In Smpn 3 Patokbeusi - Muhammad Rofi Fadhillah; Febi Kurniawan; Citra Resita (JUARA : Jurnal Olahraga, 2022)
The purpose of this study is to determine the tolerance attitude of the students of class VIII at SMPN 3 Patokbeusi in learning physical education, health and recreation. This research uses descriptive qualitative and quantitative methods. The sample is students of class VIII. The data collection process uses triangulation and statement questionnaires with the Guttman scale. The analysis of the data from the attitude indicator of tolerance using the univariate formula. The results show that the tolerance attitude of the students of class VIII at SMPN 3 Patokbeusi is very positive.